STUDENTS’ PERCEPTION IN WRITING DESCRIPTIVE TEXT - Rizki Kurnia; Evie Kareviati (IKIP Siliwangi, 2021)
In this study, the researcher used qualitative research method to find out students’ perception in writing descriptive text. The subjects of this research were the 25 students in SMPN 32 Bandung. They were 13 boys and 12 girls. To collect the data, the researcher used pre-test, post-test that given after the students had got the treatment and also questionnaire. The result of the study showed the highest score for pre-test was 84, the lowest score was 16, and the mean score was 43.2. The data showed that the students’ score still low. And the highest score for post-test was 90, the lowest score was 40, and the mean score was 68.8. It means that students improved their ability after the treatment given, and their perception in writing descriptive text was found. But the researcher indicates that the students were still in low level or their ability in writing descriptive text was still weak. Keywords: Students’ Perception, Writing, Descriptive Text